2006 International Electron Devices Meeting 2006
DOI: 10.1109/iedm.2006.346924
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electrode-Induced Strain Engineering for High Performance SOI FinFET utilizing Si (1hannel for Both N and PMOSFETs

Abstract: SEMATECH 2706 Montopolis Drive, Austin, TX 78741 1. IBM assignee, 2. Ti assignee, and 3. Freescale assignee ABSTRACT If Si (110) channel can be used for both nMOS and pMOS FinFET, the implementation of FinFET can be simplified significantly. Electron mobility degradation at Si(110) channel of finFET has been one of the major barriers in this path. We report a creative method to improve electron and hole mobilities using a novel metal electrode induced-strain engineering, which also features the effective workf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…4). With decreasing channel length, the hole mobility was enhanced more than the electron mobility, which was confirmed by piezoresistance (PR) calculation [8]. No differences in CV curve were observed with and without strain, indicating that equivalent oxide thickness and threshold voltage were not affected by the stressor layers (Fig.…”
Section: Resultssupporting
confidence: 58%
“…4). With decreasing channel length, the hole mobility was enhanced more than the electron mobility, which was confirmed by piezoresistance (PR) calculation [8]. No differences in CV curve were observed with and without strain, indicating that equivalent oxide thickness and threshold voltage were not affected by the stressor layers (Fig.…”
Section: Resultssupporting
confidence: 58%
“…This is explained by the WF lowering due to the composition or the thickness variation of the TiN gate. Previous reports show that the WF of the TiN gate is varied depending on the nitrogen concentration [13] or the TiN thickness [14]. In addition, by correlating other butterfly curves with the I-V characteristics of the FinFETs in each cell, it is concluded that the variation of the SRAM cell is due to the V th variation caused by the WFV.…”
Section: A Variability Of the Sram Cellsmentioning
confidence: 88%
“…It was reported that metal gate material deposited on top of the high-K dielectric can be made either compressive or tensile depending on the materials and the deposition conditions [51]. Owing to the close proximity of the metal films to the channel of transistors, significant amount of strain can be transferred into the channel, and therefore, additional performance benefit can be achieved by engineering MGS.…”
Section: Strain Engineering With High-k/metal Gate (Hkmg) Cmos Architmentioning
confidence: 99%